Konflik, Dialog, dan Integrasi: Sebuah Eksplorasi Filosofis tentang Hubungan Sains dan Agama - Afkarina, Miftahul; Wahyu Irawan; Abdul Haris; Abd. Malik Karim Amrullah; Dhevin MQ Agus Puspita W. (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research is a literature review conducted by searching, reading, analyzing, and synthesizing various written information sources such as books, journals, articles, and reports relevant to the research topic. This study focuses on philosophical perspectives that view human life on earth as being significantly influenced by both religion and science. While religion provides guidance and direction in life towards an ethical, moral, and civilized existence, science offers humans a wealth of knowledge. Moreover, advancements in science enable the world to discover more things that facilitate and ease human existence. The relationship between religion and science has been a subject of ongoing discussion among scholars. This relationship encompasses conflict, independence, dialogue, and integration. Religion and science are said to be in conflict due to their differing histories, methods, and fields of study, while independence suggests that they are separate entities with their own respective domains. In dialogue, religion and science offer a relationship between knowledge and faith with a more constructive interaction compared to the perspectives of conflict and independence. The integration approach, on the other hand, is understood as the process of combining and adjusting elements of both religion and science, resulting in a fusion of two distinct dimensions that ultimately achieve harmony.